A Case of IL-7R Deficiency Caused by a Novel Synonymous Mutation and Implications for Mutation Screening in SCID Diagnosis - Gallego-Bustos, Fernando; Gotea, Valer; Ramos-Amador, José T.; Rodríguez-Pena, Rebeca; Gil-Herrera, Juana; Sastre, Ana; Delmiro, Aitor; Rai, Ghadi; Elnitski, Laura; González-Granado, Luis I.; Allende, Luis M. (Frontiers in Immunology, 2016)
Reported synonymous substitutions are generally non-pathogenic and rare pathogenic synonymous variants may be disregarded unless there is a high index of suspicion. In a case of IL7 receptor deficiency SCID, the relevance of a non-reported synonymous variant was only suspected through the use of additional in silico computational tools which focused on the impact of mutations on gene splicing. The pathogenic nature of the variant was confirmed using experimental validation of the effect on mRNA splicing and IL7 pathway function. This case reinforces the need to use additional experimental methods to establish the functional impact of specific mutations, in particular for cases such as SCID where prompt diagnosis can greatly impact on diagnosis, treatment and survival.